Political and educational utopias in the training of History teachers in Barcelona and São Paulo (Práxis Educativa, 2013)
This paper presents some thoughts about political and educational utopias on the education of History teachers. Political and educational utopias are comprehended as projects for a better world based on a profound criticism of the present. The sources are testimonials from eight history/social studies teachers from the province of Barcelona and the state of São Paulo, studied as documents-monuments, based in A. Colombo, C. Dubois, C. Boto and others. The comparative analysis allows us to study the complexity of personal and ideological issues on the education of History and Social Sciences teachers. The teachers showed the desire to be democratic and they support democracy in its substantive sense, according to N. Bobbio. Keywords: Utopias. Teachers responsibility. Education of History teachers.